Toleransi Antarumat Beragama di Indonesia dari Perspektif Etika Kepedulian - Yeremias Jena (Jurnal Sosial Humaniora, 2019)
Dialogue and co-existence between religious believers have been practicedquite extensively in Indonesia, especially since the New Order era. From thebeginning, it did happen top-down because of the government's politicalstrategy to create a peaceful and stable society for the success of physicaldevelopment. However, in subsequent developments, the importance ofchanging approaches to dialogue and cooperation between religiousbelievers was considered as an urgent matter. Therefore, the activeinvolvement of citizens and the creation of social spaces for the interactionand encounter of citizens of different religions, ethnicities and cultures havebeen initiated and practiced by the government in many regions of Indonesia.Unfortunately, intolerant and exclusive attitudes among citizens still occur.By using philosophical inquiry methods to analyze various practices ofinterreligious dialogue in Indonesia, it was found that first, there has been achange in approach in interreligious dialogue in Indonesia. Second, it isincreasingly being realized that social spaces for encounters betweendifferent citizens must continue to be expanded as a medium to combatintolerant attitudes. Third, caring ethics, especially aspects of attention, canbe a moral and philosophical foundation that strengthens caring interactionsbetween citizens in the social space that has been formed.